The Role of AChE in Swimming Behavior of Daphnia magna: Correlation Analysis of Both Parameters Affected by Deltamethrin and Methomyl Exposure - Qing Ren; Ruibin Zhao; Cheng Wang; Shangge Li; Tingting Zhang; Zongming Ren; Meiyi Yang; Hongwei Pan; Shiguo Xu; Jianping Zhu; Xun Wang (Journal of Toxicology)
The unpredictable toxicity of insecticides may cause behavior disorder of biological organisms. In order to assess the role of acetylcholinesterase (AChE) in swimming behavior of Daphnia magna, a correlation analysis of both parameters in 24 h exposure of deltamethrin (DM) and methomyl (MT) was investigated. The behavior responses of D. magna in DM (13.36 μg/L and 33.40 μg/L) and MT (19.66 μg/L and 49.15 μg/L) suggested that recovery behavior in the adjustment phase was crucial, and behavior homeostasis provided them with an optimal way to achieve a wider tolerance against environmental stress. During the experiment, positive effects on AChE activity occurred in the beginning of the exposure. Even though the de novo synthesis of AChE in D. magna might help it recover, the AChE inhibition in different treatments could be observed. Some induction effects on AChE activity at the beginning of exposure occurred, and a 50% decrease may cause toxic effects on behavior. In most treatments, the results showed that both behavior strength and AChE activity stayed in the same field within a correlation circle. These results illustrated that the environmental stress caused by both DM and MT could inhibit AChE activity and subsequently induce a stepwise behavior response, though both pesticides affect it as direct and indirect inhibitors, respectively.